Pengaruh Burnout terhadap Kinerja Pegawai Badan Pengelolaan Keuangan dan Aset Daerah Pemerintah Kota Surabaya - B, Bunga; Fanida, Eva Hany; M, Meirinawati; Niswah, Fitrotun (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Burnout is a form of work fatigue that arises due to prolonged work pressure and can impact the psychological condition of employees, thus potentially reducing the level of performance in the organization, especially in public sector agencies that have a high administrative burden and work responsibilities. This study was conducted to determine the effect of burnout on employee performance at the Regional Financial and Asset Management Agency of the Surabaya City Government. The method used was a quantitative approach through a survey, with data collection using a questionnaire to 76 respondents selected through a proportionate stratified random sampling technique. Furthermore, the data obtained were analyzed using a simple linear regression test with the help of IBM SPSS Statistics software. Based on the results of a simple linear regression analysis, the burnout variable has a regression coefficient (B) of -0.292 with a significance value of less than 0.001, which indicates that burnout has a negative and significant effect on employee performance. These results indicate that the higher the level of burnout experienced by employees, the lower the level of performance produced. This finding is also supported by the results of the partial test (t-test) which shows a significant effect of burnout on performance, so that the research hypothesis stating that burnout has an effect on employee performance can be accepted. In addition, the results of the coefficient of determination (R Square) of 0.353 indicate that burnout is able to explain 35.3% of the variation in employee performance, while the remaining 64.7% is influenced by other factors outside the research model.